2003
DOI: 10.1177/0013164403258403
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Attraction to Organizations

Abstract: Organizational attractionmeasures are commonly used as surrogate assessments of organizational pursuit. Despite the range in content often encompassed by such instruments, no research has systematically examined the assumptions underlying their use. The authors address this issue by empirically distinguishing items assessing attractiveness, prestige, and behavioral intentions and by modeling their effects on organization pursuit. Undergraduates ( N= 305) were randomly assigned to recruitment literature from on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
677
0
33

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(719 citation statements)
references
References 38 publications
9
677
0
33
Order By: Relevance
“…General attractiveness is an individiual's initial attitude toward a company as a potential place of work, while prestige reflects social status of the organization such as reputation, popularity, and status (Highhouse, Lievens, & Sinar, 2003). Therefore, the results of this study showed that when considering a company as a place of work, students pay more attention to its reputation instead of their initial attitude.…”
Section: Findings On the Domains Of Oamentioning
confidence: 79%
See 2 more Smart Citations
“…General attractiveness is an individiual's initial attitude toward a company as a potential place of work, while prestige reflects social status of the organization such as reputation, popularity, and status (Highhouse, Lievens, & Sinar, 2003). Therefore, the results of this study showed that when considering a company as a place of work, students pay more attention to its reputation instead of their initial attitude.…”
Section: Findings On the Domains Of Oamentioning
confidence: 79%
“…OA was divided to 3 facets: general attractiveness, intention to pursue, and prestige (Highhouse, Lievens, & Sinar, 2003). These 3 facets were developed from several researches and then constructed to be a scale.…”
Section: Organization Attractionmentioning
confidence: 99%
See 1 more Smart Citation
“…of Highhouse, Lievens, and Sinar (2003) on 7-point Likert-type scales ranging from 1 (strongly disagree) to 7 (strongly agree).…”
Section: Study 2 Methodsmentioning
confidence: 99%
“…Five items which have received most attention from previous studies on attraction to organization (Scott Highhouse, FilipLievens & Even F. Sinar, 2003) [8] were used in this study to measure organizational attraction. The example is "For me, this company would be a good place to work."…”
Section: Methodsmentioning
confidence: 99%